Deformation structural style of the rioni foreland fold-and-thrust belt, western greater caucasus: Insight from the balanced cross-section - Alania, Victor; Melikadze, George; Pace, Paolo; Fórizs, István; Beridze, Tamar; Enukidze, Onise; Giorgadze, Anzor; Razmadze, Alexander (Frontiers in Earth Science, 2022)
The Rioni foreland fold-and-thrust belt is part of the Greater Caucasus pro-wedge and is one of the most important examples of the collision-driven far-field deformation of the Arabia-Eurasia convergence zone. Here we show the deformation structural style of the Rioni foreland fold-and-thrust belt based on seismic reflection profiles and regional balanced cross-section. The main style of deformation within the Rioni foreland fold-and-thrust belt is represented by a set of fault-propagation folds, duplexes, and triangle zone. The regional balanced cross-section shows that fault-propagation folds above the upper detachment level can develop by piggyback and break-back thrust sequences. Formation of fault-bend fold duplex structures above the lower detachment is related to piggyback thrust sequences. A balanced section restoration of compressional structures across the Rioni foreland fold-and-thrust belt provides a minimum estimate of shortening of −40%, equivalent −42.78 km. The synclines within the Rioni foreland fold-and-thrust belt are filled by the Middle Miocene-Pleistocene shallow marine and continental syn-tectonic sediments, forming a series of typical thrust-top basins. Fault-propagation folds and duplex structures formed the main structure of the thrust-top basin. The evolution of the thrust-top basins was mainly controlled by the kinematics of thrust sequences. Using end-member modes of thrust sequences, the thrust-top basins are divided into: 1) Type I-piggyback basin, 2) Type II-break-back basin, and 3) Type III—formation of thrust-top basin characterized by bi-vergent geometry and related to combined, piggyback and piggyback back thrust sequences.